Faktor yang Mempengaruhi Keputusan Mahasiswa Menggunakan Bank Syariah Indonesia (Studi Kasus : Mahasiswa UIN Syarif Hidayatullah Jakarta) - Putri, Ratu Rizka Ayu; Syahidah, Salma Nur; Zahira, Ghina; Pebrianti, Syaiha Aisyah (WANARGI : Jurnal Manajemen Dan Akuntansi, 2024)
This research aims to analyze the influence of service quality, religiosity and risk on UIN Syarif Hidayatullah Jakarta students' decisions in using Bank Syariah Indonesia (BSI) services. The research used quantitative methods with primary data obtained through questionnaires to 100 respondents selected using purposive sampling techniques. Data were analyzed using multiple linear regression via SPSS 26 software. The research results show that the three independent variables, namely service quality, religiosity, and risk, have a significant influence on students' decisions to use BSI services. The service quality variable has a significance value of 0.001 (< 0.05), religiosity of 0.000 (< 0.05), and risk of 0.015 (< 0.05). This shows that service quality, religious values, and risk perceptions play an important role in driving UIN Syarif Hidayatullah Jakarta’s students decisions to choose Bank Syariah Indonesia as a financial service provider. This research provides implications for BSI managers to continue to improve service quality, education about sharia-based financial literacy, and risk management in order to attract the interest of the younger generation as a potential market segment.